Pengaruh Penggunaan Media Animasi Powtoon Terhadap Hasil Belajar EstimasiBiaya Konstruksi di SMK Negeri 1 Sumatera Barat - Nur Arifah; Nadra Mutiara Sari; Rijal Abdullah (Jurnal Applied Science in Civil Engineering, 2020)
The background of this research is the difficulty of students in understanding the material which is not only in the form of theory but also calculations that make students think more critically to understand the lesson. In addition, it is not supported by interactive learning media to understand the material about Construction Cost Estimates. The purpose of this study was to determine the effect of using Powtoon animation media on student learning outcomes in Construction Cost Estimation subjects in the Building Modeling and Information Design (DPIB) class of SMK Negeri 1 West Sumatra. This study uses experimental research with a Non Equivalent Control Group design. The research design used 2 classes, namely class XI DPIB class A as the experimental class and class XI DPIB as the control class. The data obtained are the results of the student's pretest before being given the action and posttest after the action is taken. Hypothesis calculation using t-test obtained t count of 3.609, where the value is greater than t table of 2.039, indicating that Ho is rejected and Ha accepted. Thus it can be concluded that there is a significant influence on student learning outcomes using Powtoon animation media and those not using the Estimated Construction Cost subject for class XI DPIB at SMK Negeri 1 West Sumatra.